24/7 Therapeutic Drug Monitoring of Beta-Lactam Antibiotics with CLAM-2000 - Tatjana Khromov; Gry Helene Dihazi; Phillipp Brockmeyer; Andreas Fischer; Frank Streit (MDPI AG, 2023)
Background: The aim of this study was to evaluate the CLAM-2000 automated preanalytical sample preparation module with integrated liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS) as a method for 24/7 therapeutic drug monitoring (TDM) of beta-lactam antibiotics in routine clinical diagnostics. Methods: Method validation was performed using quality control samples. Method comparison was performed with routine samples from patients treated with beta-lactam antibiotics. Results: The determination of piperacillin, meropenem, ceftazidime, flucloxacillin, and cefotaxime was performed using D5-piperacillin and D6-meropenem as internal standards. The linearity of the method was within the therapeutic range of beta-lactam antibiotics. The imprecision and accuracy data obtained from quality control samples were within 15%, and the imprecision of patient samples on the instrument was less than the 5% coefficient of variation (CV). Internal standards stored in the instrument at 9 °C for at least one week were stable, which facilitated reagent use and storage. Conclusion: The CLAM-2000 (Shimadzu, Kyoto, Japan) provides reproducible results as an established routine instrument and is a useful tool for 24/7 TDM of beta-lactam antibiotics in routine clinical diagnostics.